Ratio between carotid artery stiffness and blood flow – a new ultrasound index of ischemic leukoaraiosis - Turk M (Dove Medical Press, 2016)
Monika Turk, Marjan Zaletel, Janja Pretnar-OblakDepartment of Vascular Neurology and Intensive Neurological Therapy, University Medical Centre Ljubljana, Ljubljana, SloveniaBackground: Ischemic leukoaraiosis (ILA) is associated with cognitive decline and aging. Its pathophysiology is believed to be ischemic in origin due to its association with cerebrovascular risk factors and similarity in location to lacunar infarctions. ILA diagnosis is still based on magnetic resonance imaging (MRI) as well as exclusion of other causes of white matter hyperintensities. So far, there are no known confirming diagnostic tests of ILA. Ultrasound studies have recently shown increased large artery stiffness, increased cerebrovascular resistance, and lower cerebral blood flow in patients with ILA. Increased arterial stiffness and decreased blood flow could have a synergistic effect, and their ratio could be a useful diagnostic index of ILA.Methods: In this post hoc analysis, we introduced new ILA indices (ILAi) that are ratios of the carotid stiffness parameters (pulse wave velocity beta [PWVβ], pressure–strain elasticity modulus [Ep], β index), and diastolic and mean blood flows in the internal carotid artery: Q-ICAd and Q-ICAm. We compared the ILAi of 52 patients with ILA and 44 sex- and risk factor-matched controls with normal MRI of the head. ILA diagnosis was based on MRI and exclusion of other causes of white matter hyperintensities. The diagnostic significance of ILAi for the prediction of ILA was analyzed.Results: All ILAi significantly differed between the groups; the most significant were PWVβ/Q-ICAd (ILA group: 1.96±0.64 vs control group: 1.56±0.40, P=0.001) and PWVβ/Q-ICAm (ILA group: 1.13±0.32 vs control group: 0.94±0.25, P=0.003). All ILAi were significantly associated with ILA (P<0.01) and were significant independent predictors of ILA. All ILAi were also sensitive and specific for predicting ILA (area under the curve: 0.632–0.683, P<0.05).Conclusion: The new ultrasound indices significantly differed between patients with ILA and the control group and were significant predictors of ILA. A combination of lower carotid blood flow and increased carotid stiffness represented as ILAi probably has a diagnostic value in patients with ILA.Keywords: carotid duplex ultrasound, carotid stiffness, carotid blood flow, white matter hyperintensities